Lack of active legitimacy in contesting non-marriage filiation: comments on Sudgment 288/2020 of the Barcelona Provincial Court, issued on May 25, 2020 - Vilar González, Silvia (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
This judgment addresses an appeal filed against a decision issued in a process to contest non-marriage filiation with respect to the father of a minor. Said procedure was initiated by the aunt of the child who exercised de facto guardianship by virtue of an irregular delegation of parental responsibi-lities carried out by the minor’s parents. In the judgment, as we will see, the Provincial Court, in addition to determining that the plaintiff did not have active legitimacy to initiate the procedure, appreciated the lack of international jurisdiction of the Spanish courts to hear the action brought, as well as an irregular situation and notorious risk in the legal situation of the minor whose parentage is debated, which requi-red the adoption of the appropriate measures.